2022
DOI: 10.1111/gcbb.12984
|View full text |Cite
|
Sign up to set email alerts
|

Stover and biochar can improve soil microbial necromass carbon, and enzymatic transformation at the genetic level

Abstract: To understand how stover incorporation affects the levels of soil carbon and its biogeochemistry process, we examined soil carbon and amino sugar carbon (AS‐C). Activity of N‐acetylglucosaminidase (NAGase) and the abundance (real‐time quantitative polymerase chain reaction, RT‐qPCR) and communities of the bacterial chitinase‐encoding gene (chiA) were monitored. We implemented a maize cropping system, which included four treatments, i.e., chopped maize stover returned directly (SD), compost produced by maize st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Partially agreeing with our hypothesis, we found that the gross N mineralisation rate in ST was significantly higher than that in CK from July to October, and the seasonal cumulative gross N mineralisation also far exceeded that in CK and BC (Table 3). The potential mechanisms may be related to successive straw return, which improved the soil organic N content (Table 2), especially the easily decomposable organic N that is readily available for mineralisation (Ren et al, 2023; Yuan et al, 2022; Zhang et al, 2022), and therefore, increased the gross N mineralisation rate under the high soil moisture and temperature conditions prevailing in mid‐summer (Figure S2); however, even biochar also had higher soil total N content than CK (Table 2), but biochar did not increase the gross N mineralisation rate on any labelling date or on a seasonal scale. This was because even the majority of plant N was maintained during the pyrolysis process, but those occurring in heterocyclic compounds (Kazi et al, 2011), and were generally considered those organic N, like biochar C, is recalcitrant and cannot be easily metabolized or assimilated by the soil microbial community or by plants (Cantrell et al, 2012; Prommer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Partially agreeing with our hypothesis, we found that the gross N mineralisation rate in ST was significantly higher than that in CK from July to October, and the seasonal cumulative gross N mineralisation also far exceeded that in CK and BC (Table 3). The potential mechanisms may be related to successive straw return, which improved the soil organic N content (Table 2), especially the easily decomposable organic N that is readily available for mineralisation (Ren et al, 2023; Yuan et al, 2022; Zhang et al, 2022), and therefore, increased the gross N mineralisation rate under the high soil moisture and temperature conditions prevailing in mid‐summer (Figure S2); however, even biochar also had higher soil total N content than CK (Table 2), but biochar did not increase the gross N mineralisation rate on any labelling date or on a seasonal scale. This was because even the majority of plant N was maintained during the pyrolysis process, but those occurring in heterocyclic compounds (Kazi et al, 2011), and were generally considered those organic N, like biochar C, is recalcitrant and cannot be easily metabolized or assimilated by the soil microbial community or by plants (Cantrell et al, 2012; Prommer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This explained why biochar failed to stimulate bacterial and fungal growth in this study. In contrast, straw application increased bacterial and fungal abundance, implying that long‐term straw amendment may be more effective than biochar in improving soil biological fertility (Xu et al, 2019; Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After collection, soil samples were then mixed, sieved, and divided into the following two parts: microbial (stored at −80°C) and soil properties (air-dried at room temperature) analyses. Soil properties, including total nitrogen (TN), total carbon (TC), NH 4 + -N (AN), available phosphorus (AP), available potassium (AK), soil organic carbon (SOC), pH, water content (WC), and bulk density (BD), were determined in accordance with our previous work (Zhang et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The introduction of engineered C materials (e.g., BC and microplastics) inevitably influences the composition and stability of the soil C pools. Typically, a single application of BC increases MNC accumulation by 10–20%, whereas multiple BC applications over a decade-long time frame have been reported to increase MNC by 21–59% . However, some studies have reported a decrease in amino sugar and MNC contents following BC addition.…”
Section: Introductionmentioning
confidence: 99%